Impact commitment to business ethics and social responsibilities in light of e-business on financial performance (field study on a sample of Jordanian commercial banks) - Ahmed Yosef Doden; Hani Saeed Abdeh (Iraqi Journal for Administrative Sciences, 2025)
This study aims to identify the impact of commitment to social responsibility and business ethics in the Jordanian commercial banks on financial performance, and the extent of the difference between the commercial banks of Jordan in the practice of social responsibility and business ethics. Has been developed theoretical framework for the study by reviewing the literature in the field of social responsibility and business ethics, the elements have been identified to measure the variables of social responsibility and business ethics, and used 4 indicators to measure the financial performance variable, Were collected preliminary data for the study through the design of identification especially for this study and distributed to a sample of 500 employees in 5 commercial banks selected sample representative of the commercial banks of Jordan, was recovered 480 to identify them and the exclusion of 30 questionnaires to non-viability, as analyzed through the use of statistical methods the various indicators of descriptive statistics to describe the reality of commitment to social responsibility and business ethics in commercial banks, and statistical methods Alastdala to analyze the relationship between independent variables and variable financial performance. The results of the analysis that there is a clear commitment by the departments of Jordanian Commercial Banks included in the study of social responsibility and business ethics, and the presence of statistically significant relation strong between a commitment to both social responsibility and business ethics and financial performance of commercial banks, as shown by the existence of differences in the degree of commitment to the commercial banks responsible social and business ethics in its dealings and banking activities Based on the findings of the study the researchers recommended that further research into the relationship between commitment to social responsibility and business ethics and indicators of non-financial performance of banks and the development of a Charter of commitment to social responsibility and business ethics and intensify the training of personnel on the use of technology to customer service and behavioral aspects of banking.